Perancangan Motorcycle Lift dengan Mempertimbangkan Anthropometri Sebagai Alat Bantu Servis Sepeda Motor - Rahmaniyah Dwi Astuti; Ilham Priyadithama; Gamma Wisnu Nurcahyo (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2012)
This research is about the improvement of working posture by implementing a tool design. In the previous condition at the small workshop, Loh Jinawi, the working postures of the mechanic’s body when doing motorcycle service was not ergonomics and potentially caused pain or even injure in afterwards the day. By Nordic Body Map equipped questionnaire, the exact body parts which were affected by these working positions were known. On the other hand, there was a REBA method that used to measure how much risks that borne by the mechanic for these postures. Considering the condition of the workshop, there was no solution to fix the problem except using a specifically designed motorcycle lift. We transformed the problem information from our preliminary study into the design requirements of the tool. The tool was developed by anthropometry consideration. The final REBA evaluation showed that the tool could significantly reduce the risks.